(untitled) (European Journal of Health Research, 2019)
This research work was in function to determine the prevalence of burnout syndrome and its relation with coping strategies with a sample of 142 physicians. The instruments used were: Sociodemographic questionnaire [Ad hoc], Maslach Burnout Inventory [MBI] Maslach and Jackson (1986); and COPE-28 [Brief COPE] Carver (1997). In relation to the prevalence of burnout syndrome, 2.8% was identified. The high levels of emotional exhaustion were 25.8%, in depersonalization the high score was 17.6% and with a low personal achievement of 61.2%. The coping strategies that presented a mean greater than 4.5 and a standard deviation 1.9 were, positive rethinking, acceptance, planning and instrumental support in terms of the correlation between coping strategies and burnout. There is a high level of significance with: self-management (142)= - 14.7 p <0.001, active coping r (142)= -.313 p ?